Bio antagonistic Analysis of Trichoderma sp. as Biofertilizer Agent for Supporting Sustainable Agriculture in Indonesia - Aidha Zulaika; Darmono Taniwiryono; Sari Sekar Ningrum; Revi Meliyani; Bunga Maulida (Universitas Ibn Khaldun Bogor, 2024)
Nowadays plantation has change to more sustainable agricultural system towards effectivity, smart system and not only environmentally friendly but also in sustainability aspects. This study aims to explore Trichoderma as biofertilizer with bioantagonistic ability. The experiment design to test Trichoderma against Fusarium Oxysporum (Wilt Desease) and Thrips (pathogen) in aclimatisation test in tomato and chili plant. The result in antagonistic against Fusarium, T. harzianum B and T. cacao 29 have good inhibitory, namely around 70% of the resistance percentage. While T. Koninggii or T. Pseudokoningii (DT 38) was the weakest. Based on that Trichoderma approved has bioantagonistic ability against Fusarium invasion. But for large scale implementation, formulation and perfection microbial isolate are needed.